The Challenge of Fiscal Adjustment in a Democracy : The Case of India - Hausmann, Ricardo (IMF Working Papers; Working Paper ;, 2004)
India's fiscal problem has deep roots in its federal fiscal system, where multiple players find it difficult to coordinate adjustment. The size and closed nature of the Indian economy, aided by its deep domestic capital market and large captive pool of domestic savings, has disguised the cost of fiscal laxity and complicated the building of a consensus on reform. The new fiscal responsibility act establishes a new rules-based system to overcome this coordination failure. To strengthen the framework, we recommend an autonomous scorekeeper and the extension of similar rules to the state governments as part of a comprehensive reform of the federal system.